The effects of adenine nucleotides on carbohydrate metabolism in pigeon-liver homogenates - Gevers, W. (1966)
1. The effects of added AMP on carbohydrate metabolism were investigated in pigeon-liver homogenates, which can degrade glucose and synthesize it from lactate. Suitable experimental conditions were established for studying such effects, including the addition of P(i) (20mm) to stabilize adenine nucleotides and supplementation with NAD(+) (0·5mm). 2. Lactate increased the rate of oxygen consumption and kept the concentration of ATP high and that of AMP relatively low. 3. Added AMP (1·25–5mm) raised the net rate of carbohydrate removal and inhibited the net formation of glucose from lactate, as well as the incorporation of lactate into glucose. These effects were accompanied by a fall in the concentrations of hexose 6-phosphates and a rise in those of fructose diphosphate and triose phosphates. When the activity of glyceraldehyde 3-phosphate dehydrogenase was limited experimentally by a low concentration of NAD(+) or when it was blocked by iodoacetate, the accumulations of fructose diphosphate and triose phosphates were large and accounted for most of the carbohydrate degraded in the presence of AMP. 4. AMP also inhibited the conversion of pyruvate into phosphoenolpyruvate. Data on the concentrations of pyruvate, phosphoenolpyruvate and intermediates of the tricarboxylic acid cycle, as well as on isotope distribution, suggest that the effect was due to inhibition of phosphoenolpyruvate carboxykinase. 5. The results indicate that in the homogenates phosphofructokinase and fructose diphosphatase, controlled in their activity by adenine nucleotides and other cell constituents, are enzymes which regulate the direction of carbohydrate metabolism (degradation or synthesis) in the liver. 6. It is suggested that active transport of adenine nucleotides, citrate, Mg(2+), Ca(2+), P(i) and other cell constituents may play a role in regulating the activity of enzymes which are affected by these substances. 7. A procedure is described for generating alkali in a closed manometer vessel, by mixing mercuric oxide and a solution of sodium iodide, for use in a method for measuring the oxygen consumption at physiological bicarbonate concentrations.